Tinjauan Yuridis Penarikan Kendaraan Bermotor Akibat Dari Kredit Macet: Studi Kasus Adira Finance Cabang Mataram - Novi Zanta Putri Dalla; Shinta Andriyani (Private Law, 2022)
The purpose of this study is to find out the dispute resolution for bad credit in the finance company that implemented in Adira Finance, and find out the procedure the Motor Vehicle Withdrawals based on the agreement between consumers and finance company. This research uses normative and empirical legal research methods, which use the statute approach, the conceptual approach, and the sociological approach. Based on the result of this study, the researcher has concluded that the fiduciary registration is regulated in Article 11 until the Article 18 Act Number 42 of 1999 concerning the Fiducia Guarantee. Based on Article 11 Act of Fiduciary, the fiduciary object should be registered. The registration of the Judiciary Guarantee has been registered by a creditor, the party by power of attorney, or the other parties. Furthermore, the Adira Finance dispute resolution has implemented a warning letter to the debtor either formally or non-formally. A written warning is formally called a summons.